Methodological Background and Foundations of the Non-Material Theory of the Psyche - Reshetnikov, Mikhail (Advances in Social Sciences Research Journal, 2019)
In this paper, a number of outdated but still prevailing medical doctrines are critically reviewed, in particular, Hippocrates’s hypothesis of the brain as a repository of all mental processes; I.M. Sechenov’s hypothesis of the psyche as a derivate of the brain reflexes; I.P. Pavlov’s hypothesis of the higher nervous activity as an equivalent of the psyche. In his research, the author refers to studies of feral children, studies of memory and subliminal perception, discovery of mirror neurons and contemporary views of the academic science on information. The author proves the non-materiality of the psyche and the role of the brain as a biological interface between the ideal and the real. The new approach would require changing the traditional paradigm as well as all our approaches to studying the psyche and treating mental disorders.